Diálogos sobre a relevância social da Associação Beneficente Floresta Imperial ABEFI: a publicidade cívica da diaconia - Teixeira, Helio Aparecido (2010)
The present dissertation traverses now about the Associação Beneficente Floresta Imperial, ABEFI, Novo Hamburgo, Rio Grande do Sul, linked to the Comunidade Evangélica Floresta Imperial, CEFI. The survey of deductive character wants to focus on the characteristics of wants to put focus on the characteristics of diakonia practiced in the community context and its social relevance to the surroundings which include the region of the old fourth ward Floresta Imperial District of New Hamburg, elevated to the category of Industrial District (Cluster) in the 1960s with the implementation of export immediate policies by the Brazilian Government. From the migration context of the theological traditions of the Evangelical- Lutheran families, the great culture of cattle in Rio Grande do Sul and the industrialization of Vale do Sinos, the objective is to list some possibilities for reading the content of formal social relevance ABEFI from which was named publicidade cívica. The intention is to analyze the elements that make up the conjunctural that that allowed the affinity of various devices to form certain social rationally to act towards a certain behavior.